THE EFFECT OF THE PRELOADING SYSTEM ON THE SHEAR STRENGTH VALUE OF PEAT SOIL: PENGARUH SISTEM PRELOADING TERHADAP NILAI KUAT GESER TANAH GAMBUT - Tarigan, Susi Aditya (UPMI Proceeding Series, 2023)
Before permanent development can be carried out, the peat soil needs to be burdened. This method is called preloading. The purpose of preloading is to reduce initial consolidation settlement, namely by preloading the soil before construction is carried out. The advantage of preloading, apart from reducing settlement, is also increasing the bearing capacity of the soil. The bearing capacity parameters can be determined from the shear strength value, therefore it is necessary to study the initial load of peat soil to find out how optimal the initial load (preloading) is and how long the initial loading time is to increase the shear strength value of peat soil. The preloading model used is through a gradual loading system with pressures of 3.02 kPa, 6.05 kPa, 9.07 kPa, and 12.09 kPa. Each load is given gradually over one day and one week. This research was carried out through modeling tests in the laboratory using a test tank measuring 150 cm x 180 cm x 70 cm. The load used is steel nako measuring 4 cm × 1.9 cm × 1.9 cm. and the main medium is peat soil. The shear strength test is carried out after the initial loading to obtain shear parameters which include the cohesion value (c) and the friction angle value in the soil (ϕ). Preloading can increase the shear strength of peat soil. This is obtained from increasing cohesion and friction angles in the soil. An increase in soil cohesion occurs during preloading for a short time, while an increase in the friction angle in the soil occurs over a longer time. This is influenced by the release of water in the soil pores in line with the compression of the peat soil. Longer preloading results in coarser soil grains, so that the friction angle value becomes higher and conversely soil cohesion becomes smaller.